1991
DOI: 10.1111/j.1365-2885.1991.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin pharmacokinetics in diabetic dogs

Abstract: Reduction of the prolonged terminal elimination phase of gentamicin may be caused by diabetes mellitus, irrespective of the model of diabetes. To test this hypothesis, Five normal dogs, three dogs with alloxan‐induced diabetes mellitus, and four dogs with naturally occurring diabetes mellitus (all of which were given exogenous insulin to control hyperglycemia) were given 4.4 mg/kg gentamicin intravenously. Serum pharmacokinetics were analyzed using noncompartmental pharmacokinetics assuming a sum of exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In contrast to the present study, in previous studies in which blood was sampled for 8 h or less or the detection limit of the assay used was greater than 0.1 g/ml, a twocompartment open model usually described the pharmacokinetics of gentamicin in plasma adequately (4). In this study, the pharmacokinetic parameters reported for the central and shallow compartments in control dogs are similar to those previously reported (3,14,15). A slow elimination phase of a threecompartment open model was very clearly demonstrated by Brown et al (3) with sample time points between 12 and 192 h postinjection.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast to the present study, in previous studies in which blood was sampled for 8 h or less or the detection limit of the assay used was greater than 0.1 g/ml, a twocompartment open model usually described the pharmacokinetics of gentamicin in plasma adequately (4). In this study, the pharmacokinetic parameters reported for the central and shallow compartments in control dogs are similar to those previously reported (3,14,15). A slow elimination phase of a threecompartment open model was very clearly demonstrated by Brown et al (3) with sample time points between 12 and 192 h postinjection.…”
Section: Discussionsupporting
confidence: 79%
“…The pharmacokinetics of gentamicin in the dog have been described previously. These reports describe data which satisfy either two-compartment (14,15) or three-compartment (3) open models. In contrast to the present study, in previous studies in which blood was sampled for 8 h or less or the detection limit of the assay used was greater than 0.1 g/ml, a twocompartment open model usually described the pharmacokinetics of gentamicin in plasma adequately (4).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma elimination phase (p phase) is correlated well with GFR in the animal species (Sojka & Brown, 1986;Frazier et al, 1988); as $hewn in Table I, t,/p in normal animals range from 1 h in dogs Brown et al, 1991) and rabbits (Huang et ul., 1979), 1.25 h in cats (Short et al, 1986;Jernigan et al, 1988a), 1.35 h in hawks (Bird et al. 1983).…”
Section: Gen(amuinmentioning
confidence: 99%
“…The presence of a deep-compartment and a three-compartment model of gentamicin disposition was suggested (3,24,27), and in some studies a terminal half-life (t 1/2 ) of more than 100 h was observed (3,20,21). However, other reports concluded that a two-compartment model best described gentamicin pharmacokinetics and were unable to observe the deep compartment (6,17,18).…”
Section: ؊1mentioning
confidence: 99%